2020
DOI: 10.1029/2019ja026708
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Effects During the Total Solar Eclipse Over Southeast Asia‐Pacific on 9 March 2016: Part 1. Vertical Movement of Plasma Layer and Reduction in Electron Plasma Density

Abstract: We report our investigation of ionospheric effects that occurred during a total solar eclipse over the Southeast Asia-Pacific region on 9 March 2016. In particular, here we examine rapid uplift of the ionospheric F-layer during the eclipse, and reductions of ionospheric plasma density in areas around the eclipse totality. This study used data from ionosondes at Biak and Guam, as well as data from a bistatic HF radio link (∼1300 km apart, cutting across the eclipse totality trajectory) between Biak and Manado. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…Combined with the curl‐free requirement for the electric field, this would produce a corresponding zonal electric field as an edge effect and would drive an enhanced PRE‐like vertical drift (Eccles, 1998; Rishbeth, 1971b, 1971a). Both our results in Figure 10b, along with previous observations and numerical simulations, have verified that solar eclipses can generate a considerable enhancement of the equatorial eastward electric field and upward plasma drift, especially in the heading (eastern) region of obscuration (Chen et al, 1971a; Dear et al, 2020; Goncharenko et al, 2018; Tsai & Liu, 1999). Under these conditions, the enhanced electric field and upward plasma drift would amplify the equatorial fountain effect and more rapidly evacuate the lower part of the F region (Tomás et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Combined with the curl‐free requirement for the electric field, this would produce a corresponding zonal electric field as an edge effect and would drive an enhanced PRE‐like vertical drift (Eccles, 1998; Rishbeth, 1971b, 1971a). Both our results in Figure 10b, along with previous observations and numerical simulations, have verified that solar eclipses can generate a considerable enhancement of the equatorial eastward electric field and upward plasma drift, especially in the heading (eastern) region of obscuration (Chen et al, 1971a; Dear et al, 2020; Goncharenko et al, 2018; Tsai & Liu, 1999). Under these conditions, the enhanced electric field and upward plasma drift would amplify the equatorial fountain effect and more rapidly evacuate the lower part of the F region (Tomás et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…For example, how does the equatorial dynamo change due to the impact of a solar eclipse? In particular, the electrodynamics of the ionospheric fountain mechanism could be complicated by solar eclipse due to conductivity variations, since the magnitude of eclipse‐associated TEC depletion at equatorial latitudes can reach more than 40%, larger than those at midlatitudes (Dear et al, 2020; Huang et al, 1999; Tsai & Liu, 1999). Moreover, to what degree is the equatorial ionization anomaly (EIA) modified by a solar eclipse?…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding Ne diffusivity is 6.25 𝐴𝐴 × 10 12 electrons/m 2 s −1 (10 16 electrons/m 2 𝐴𝐴 × 1.5 TECU/3,600 s). Numerous studies reported the layer uplift or occurrence of strong vertical drift during solar eclipses (e.g., Dear et al, 2020;Pradipta et al, 2018;Verhulst et al, 2016;W. Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the neutral wind transport, the eclipse‐induced ionospheric equatorial electric field perturbations can also possibly affect the ionospheric variation. Previous observations and numerical simulations suggested that solar eclipses can induce a considerable increase in the eastward equatorial electric field, which then modifies the ionospheric variations by the upward E × B drifts (Chen et al, 2019; Dear et al, 2020; Goncharenko et al, 2018; St‐Maurice et al, 2011; Tsai & Liu, 1999). As shown in Figure 9, the h m F 2 at Guam which is close to the magnetic equator evidently increased from 300 to 350 km around the onset of the eclipse and then decreased rapidly during the eclipse, which was different as compared with that before and after the eclipse day and the reference.…”
Section: Discussionmentioning
confidence: 99%